'n Evaluasie van die technikon· opleiding van voornemende skakelpraktisyns - Betsie Ferreira (Communicare)
The purpose of this study was to evaluate the training programme in public relations offered by Technicon to determine whether it adequately prepares candidates for the public relations sector. To reach this objective, a literature study was undertaken in order to identify technikon training requirements as well as professional training requirements in public relations. This study concentrated mainly on South African and American literature, the latter being accepted as a role model for public relations curricular. The systems perspective, and more specifically Files" (1984) macro systems model for public relations curricula. Serve as theoretical basis for this study. The literature study was supplemented by interviews with former students and employers in the field of public relations. The study included an analysis of a national mail-questionnaire survey sent to 403 persons who have obtained the National Diploma in Public Relations. The study identified weaknesses and shortcomings in the current training programme In conclusion, recommendations to improve the current programme, as well as guidelines for the curriculum planning of higher qualifications in public relations at Technicon, were offered